1997
DOI: 10.1109/77.620908
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxygen partial pressure during heat treatment on the microstructure of dip-coated Bi-2212/Ag and Ag alloy tapes

Abstract: Abstract---The evolution of the microstructure during heat treatment was investigated for dip-coated BizSr2CaCu20y(Bi-2212)/Ag and Ag alloy tapes as a function of temperature and oxygen partial pressure(Poz=0.01, 0.21 and 1 atm) using quenched and fully-processed tapes. The microstructures were essentially the same for Bi-2212 on pure Ag and on the Ag alloy. Although the melting temperature of Bi-2212 increased with increasing Po*, the solidification temperature(T,,I) of Bi-2212 for Poz=0.21 atm was higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…However, it does not reach 91 K, as for the films processed in oxygen. This behaviour indicates that the poor transport properties of as-sintered thick films are due not only to oxygen deficiency in the structure, but also to weak grain coupling [15]. Annealing in O 2 at high temperatures improves weak grain coupling.…”
Section: Superconducting Propertiesmentioning
confidence: 96%
See 1 more Smart Citation
“…However, it does not reach 91 K, as for the films processed in oxygen. This behaviour indicates that the poor transport properties of as-sintered thick films are due not only to oxygen deficiency in the structure, but also to weak grain coupling [15]. Annealing in O 2 at high temperatures improves weak grain coupling.…”
Section: Superconducting Propertiesmentioning
confidence: 96%
“…Partial melting and solidification of Bi 2 Sr 2 CaCu 2 O y strongly depends on processing parameters such as maximum melting temperature, time of reaction and solidification rate [13]. The partial oxygen pressure also affects the reaction kinetics during partial melting and phase growth [14,15]. Variations of the partial oxygen pressure and the processing temperature lead to the formation of different phases.…”
Section: Introductionmentioning
confidence: 99%
“…The morphology and chemical reactivity of the present phases when Bi2212 begins to form have significant impact on the electrical properties of the wire as they are critical for forming the final microstructure. Presently, PMP is performed in flowing oxygen (P O2 = 1 atm) because it results in the highest J c [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, all of them have been obtained in polycrystalline systems, which are significantly influenced by the presence of highly defective regions like grain boundaries. In fact, Fujii et al [10][11][12] proved that such boundaries can show the presence of amorphous areas, whose features are controlled by the oxygen partial pressure during the crystallization process. On the other hand, the measurements by Prouteau et al [13] have shown that the grain boundaries are characterized by extended non-stoichiometric zones, depleted in oxygen, which has also been confirmed from an electronic point of view by the Josephson junction experiments on YBCO [6].…”
Section: Introductionmentioning
confidence: 99%